Studi Kebiasaan Sarapan Pagi dan Pengaruhnya Terhadap Status Anemia dan Prestasi Belajar Anak Sekolah Dasar di Wilayah Pesisir dan Non Pesisir - Ivanna Sardila Leba; Stefanus Manongga; Daniela Boeky (Lontar : Journal of Community Health, 2019)
Breakfast is an activity of eating and drinking starting from waking up in the morning and fulfilling 15-30% of daily nutritional needs. Breakfast could increase the concentration of learning and it believed could improves children's learning achievement. Delaying breakfast could increase the risk of anemia in children. People in coastal and non-coastal areas have different food supplies according to the environment and natural products that exist and it might make the difference of provision of the breakfast because it was related to the provision of the food. The purpose of this study is to analyze the influence of breakfast habits on anemia status and learning achievement of elementary school students at coastal and non-coastal area. This study used cross sectional research design and the population of this study were all elementary school students at Kupang city. The determination of this research samples used Slovin formula with a sample size of 100 respondents. And for the statistical tests used analysis of Simple Loistic Regression Test and Whitney Mann test. The statistical test results showed that there was an influence between breakfast habits frequency (p = 0,000), energy contribution (p = 0,000) and protein (p = 0,020) on anemia status. Therefore research findings was shown an influence between the contribution of energy (p = 0.032) and protein (p = 0.004), learning achievement (p = 0.409) on student’s learning achievement. Otherwise, there was no influence between anemia status and learning achievement (p = 0.520). The results of the Mann Whitney test showed that there was no difference between breakfast habits, anemia status and learning achievement in coastal and non-coastal areas.